2013
DOI: 10.1186/1471-2431-13-189
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of academic performance in children with sickle cell anaemia

Abstract: BackgroundSome factors are known to influence the academic performance of children with Sickle Cell Anaemia (SCA). Information on their effects in these children is limited in Nigeria. The factors which influence academic performance of children with SCA in Enugu, Nigeria are determined in this study.MethodsConsecutive children with SCA aged 5–11 years were recruited at the weekly sickle cell clinic of the University of Nigeria Teaching Hospital (UNTH) Enugu, Nigeria. Their age- and sex- matched normal classma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…In contrast, mothers who have difficulties adjusting to their child's illness can cause the child to feel nervous, humiliated, or guilty (Barbarin & Christian, 1999). Contrary to most research findings, recent studies have found that the quality of life of children with SCD was not lower than that of healthy children (Constantinou, Payne, & Inusa, 2014), nor was their academic performance affected by school absenteeism (Ezenwosu, Emodi, Ikefuna, Chukwu, & Osuorah, 2013).…”
Section: Quality Of Life In Children With Scdmentioning
confidence: 90%
“…In contrast, mothers who have difficulties adjusting to their child's illness can cause the child to feel nervous, humiliated, or guilty (Barbarin & Christian, 1999). Contrary to most research findings, recent studies have found that the quality of life of children with SCD was not lower than that of healthy children (Constantinou, Payne, & Inusa, 2014), nor was their academic performance affected by school absenteeism (Ezenwosu, Emodi, Ikefuna, Chukwu, & Osuorah, 2013).…”
Section: Quality Of Life In Children With Scdmentioning
confidence: 90%
“…Although the adolescents had reported school absenteeism due to illness (Schwartz, Radcliffe, & Barakat, 2009 ), they had academic success. It is possible that family, peer, and teacher support aided this process as the literature shows that academic success is positively associated with social class in SCD (Ezenwosu, Emodi, Ikefuna, Chukwu, & Osuorah, 2013 ). Unfortunately, social class was not accessed in this study, but it might have contributed to the positive academic outcome reported in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights that SCD in Campina Grande, Paraíba and its surrounding cities occurs predominantly amongst the mixed and black populations, and evidence shows a clear social vulnerability, which already was demonstrated by other studies. 8,[16][17][18] The affected population occupies the base of the social pyramid and exhibits the worst socioeconomic, epidemiological and educational indicators; it gains the lowest salary, it has the highest unemployment rate, the worst access to healthcare and the lowest participation of GDP, and for this reason it is a victim of the institutional racism, with differenti-ated distribution of services, benefits and opportunities, generating inequalities and inequities. 16 The predominance of SCD among the underprivileged is well documented in many studies on the subject, [18][19][20][21] as well as the low schooling level of caregivers; in some publications, more than 50% of the responsible guardians did not concluded the elementary level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2013, hydroxyurea has been incorporated into standard treatment norms and is the only medication currently affecting the quality of life of patients with SCD, significantly reducing morbimor-quotient 18 and their worst socioeconomic status. 18,24 The psychosocial consequences faced by these individuals must be taken into consideration; they are victims of stigmatization resulting from a triple association between skin color -social classchronic and severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation